PENGARUH KOSENTRASI BIOURINE SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) - Luh Putu Yuni Widyastuti; Ramdhoani; I Ketut Sumantra; Patrianus Hadun (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
Brassica juncea L. or commonly called mustard greens is one of the most popular types of vegetables in Indonesia, because this mustard is one of the varieties that contain various health benefits. The objectives of this research are 1). Knowing the effect of giving cow biourine concentration on the growth and yield of mustard plants. 2). Determine the effect of giving the best concentration of cow biourine on the growth and yield of mustard plants. This study used a Randomized Block Design (RBD) method with six treatments, namely the control treatment (B0), the concentration of biourine 100 ml/1 liter of water (B1), the concentration of 100 ml/1 liter of water (B1). Biourine 200 ml/1 liter water (B2), biourine concentration 300 ml/1 liter water (B3), biourine concentration 400 ml/1 liter water (B4), and biourine treatment 500 ml/1 liter water (B5) each treatment was repeated four times so that the total number of treatments was 24. In the test of the effect of bovine biourine concentration on mustard plants, the application of 500 ml/1 liter of water bovine biourine gave the best growth results for all parameters observed, namely; Plant height (cm), Number of leaves (strands), Leaf area (cm2), fresh weight of plant roots (g), fresh weigght withouat plant roots (g), Total fresh weight of the plant (g),Oven dry weight of plant roots (g), Oven dy weight withouat plant roots (g), and Total oven dry weight of plants (g).